PENGARUH KONSENTRASI PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL PADA 3 (TIGA) KULTIVAR TANAMAN KACANG HIJAU (Vigna radiata L.) - Tadjudin Surawinata; Umi Trisnaningsih; Meiza Maajid Panuntas (Program Studi Ilmu Pertanian Pascasarjana UGJ, 2017)
This study aimed to determine the effect of liquid organic fertilizer on the growth and yield of mung bean (Vigna radiata L.) cultivars Wallet, Vima-1, and Murai. The experiment was conducted in UPTD Seed Crops Development Center (BPBD) Plumbon Cirebon, from March to May, 2016.The method used in this research is the experimental method. The experimental design used was a randomized block design (RBD). This experiment consisted of 12 combinations of treatments, namely: A (POC concentration of 6 ml / 1 liter of water at Cultivars Swallow), B (POC concentration of 6 ml / 1 liter of water at Cultivars Vima-1), C (POC concentration of 6 ml / 1 liters of water on the cultivar Murai), D (POC concentration of 8 ml / 1 liter of water at cultivars Swallow), E (POC concentration of 8 ml / 1 liter of water at cultivars Vima-1), F (POC concentration of 8 ml / 1 liter water cultivars Murai), G (POC concentration of 10 ml / 1 liter of water on the cultivar Swallow), H (POC concentration of 10 ml / 1 liter of water on the cultivar Vima-1), I (POC concentration of 10 ml / 1 liter of water on the cultivar Murai) , J (POC concentration of 12 ml / 1 liter of water at cultivars Swallow), K (POC concentration of 12 ml / 1 liter of water at cultivars Vima-1), and L (POC concentration of 12 ml / 1 liter of water at Murai cultivars).The results showed that there is a significantly effect between mungbean cultivars and liquid organic fertilizer (Bio-agro) to plant height at 28 DAP, leaf area index at 28 DAP, dry seed weight per plant, and dry seed weight per plot. Dry grain weight per plot the best is on the concentration of liquid organic fertilizer (Bio-agro) 10 ml / l given in the cultivar Vima-1 to produce green beans 0.38 kg / plot or the equivalent of 1,266 t / ha